HUBUNGAN KEPEMIlIKAN JAMBAN DENGAN TINGKAT PENGETAHUAN DAN PENDIDlKAN MASYARAKAT (STUDI 01 OESAMENOAlAN KECAMATANWINONGAN KABUPATEN PASURUANTAHUN 2012) - Alif Nuril Zainiyah; Sri Mardoyo; Marlik Marlik (GEMA LINGKUNGAN KESEHATAN, 2013)
Family toilet is an important and necessary part of public health improvement. In some areas,fecal disposalfacility that satisfy health requirements were not available as expected, especially among thelow economic level of the society, and the cost to build latrines becomes a barrier for families. Besidethis,other factors come into play such as the effective knowledge on health issues was inferior, as well as theever present habit unhealthy defecation in the community.Statistical analysis in this research relied on the use of chi-square test where primary datacollection was carried out by meansof observations and the use of questionnaires returned by 89 heads offamilies. Secondarydata were obtained from Mendalan village, Winongan subdistrict, Pasuruanregency.A portion of the community (19.1%) have poor understanding with regard to latrine and itsownership. Significant portion of the community (45%) did not finish their primary education. Whereas asmany as 71.9% of the the community did not have latrines. It was noted that there was no relationshipbetween levels of education and latrine ownership at a chi-square p a (0/233 0/1); and also there is norelationship between the community level of knowledge on latrines with latrine ownership indicated by achi-square of p 0(0/114 0/1).The study recommends to conduct the community awareness raising leading to initiation ofrevolving fund drive for latrine construction; to employ workers on regular basis to clean up theenvironment surrounding Mendalan village of Winongan subdistrict and to strengthen the role ofcommunity leaders in community mobilization.